In silico Docking Studies between Atorvastatin and Human Cholesteryl Ester Transfer Protein (CETP) Facilitating the Conversion of Triglycerides Found in VLDL into Cholesterol Esters Found in HDL of Pan troglodytes - R.Sathya; .J, Thirumagal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The focus of the current human genomics research is Pan triglodytes, the animal with the highest sequence homology to Homo sapiens. Our research investigation focuses on the Pan triglodytes gene because of this. A plasma protein called cholesterol ester transfer protein (CETP) helps to change the triglycerides present in very low density lipoprotein (VLDL) into the cholesterol esters present in high-density lipoprotein (HDL). Several investigations have shown that CETP is the direct cause of atherosclerosis. Using 3D In silico drug docking techniques, we alter the putatively altered target protein CETP and examine its interactions with atorvastatin. To carry out drug docking techniques, the translated amino acid sequence and three-dimensional chemical compound were obtained from the NCBI database. Advanced 3D molecular imaging capabilities were used in post-docking experiments. The results of the docking study made it abundantly evident that atorvastatin directly decreases amino acid mutational sites. Using ideas from molecular dynamics techniques, the electrostatic interaction between atorvastatin and CETP is depicted in three dimensions. Lastly, we can state that atorvastatin, an anti-cholesterol medication, helps to prevent heart attacks and other cardiovascular illnesses. Our goal is to provide an illustration of the molecular mechanism that atorvastatin uses to interact with CETP. Pharmacological research investigations in humans can be conducted by analysing the interaction of Pan triglodytes with CETP and correlating it with human atherosclerosis.